Faktor – Faktor yang Mempengaruhi Pemberian Imunisasi Pcv (Pneumococcal Conjugate Vaccin) Pada Bayi - Bina Aquari; Heru Listiono (STIKes Budi Mulia Sriwijaya, 2023)
The PCV immunization program or administration of the PCV vaccine or pneumococcal conjugate vaccine has been carried out in stages since 2017. Free PCV immunization is provided by the government. The World Health Organization (WHO) has also recommended that the PCV vaccine be included in routine immunization programs for children around the world. According to (WHO, 2020) pneumonia killed 740,180 children under the age of 5 years in 2019, accounting for 14% of all deaths of 2 children under five years but 22% of all deaths in children aged 1 to 5 years. The infant mortality rate due to pneumonia in Indonesia still tends to fluctuate from 2011-2021. The highest CFR occurred in 2013 at 1.19%. Meanwhile, the lowest CFR was 0.08% in 2014 and 2018. Based on a preliminary study at the Anisa Clinic/BP, Banyuasin Regency, 35 parents have given the PCV vaccine to their children in the last 6 months. Based on the results of interviews with 30 respondents, mothers said they did not understand clearly what the PCV vaccine was and how to prevent pneumonia in infants. Based on this background, the researcher was interested in examining the title of the factors that influenced PCV immunization at the Anisa Clinic/BP, Banyuasin Regency. This research is a quantitative descriptive study with a cross sectional approach. The research was conducted at the Anisa Clinic/BP, Banyuasin Regency. Data collection was carried out from December 2022 to April 2023 using a purposive sampling technique of 30 respondents. The independent variables in this study were educational variables, knowledge and motivational variables while the dependent variable was giving PCV immunization to infants. Measuring tool used is a questionnaire. Statistical tests were carried out on 30 respondents using univariate analysis and bivariate analysis. The results of bivariate analysis using the chi square formula found that there was a significant relationship between mother's education, mother's knowledge and mother's motivation with giving PCV immunization to infants. mother with a p value = 0.001, it can be concluded that statistically at 5% alpha there is a significant relationship between education, knowledge, mother's motivation and giving PCV immunization to infants. Suggestions in this study are the need to increase counseling about PCV immunization at posyandu - posyandu in the working area of ​​the local puskesmas, especially midwives need training related to immunization to increase knowledge about immunization given the large number of new vaccines currently available